Correction: Outcomes among children and adults at risk of severe dengue in Sri Lanka: Opportunity for outpatient case management in countries with high disease burden. - Champica K Bodinayake; Ajith DeS Nagahawatte; Vasantha Devasiri; Niroshana J Dahanayake; Gaya B Wijayaratne; Nayani P Weerasinghe; Madureka Premamali; Tianchen Sheng; Bradley P Nicholson; Harshanie A Ubeysekera; Ruvini Mp Kurukulasooriya; Aruna D de Silva; et al. (Public Library of Science (PLoS), 2022)
[This corrects the article DOI: 10.1371/journal.pntd.0010091.].